2022
DOI: 10.1111/jeb.14102
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection shapes ornament allometry in functionally convergent Caribbean Anolis and Southeast Asian Draco lizards

Abstract: Visual ornaments have long been assumed to evolve hyper‐allometry as an outcome of sexual selection. Yet growing evidence suggests many sexually selected morphologies can exhibit other scaling patterns with body size, including hypo‐allometry. The large conspicuous throat fan, or dewlap, of arboreal Caribbean Anolis lizards was one ornament previously thought to conform to the classical expectation of hyper‐allometry. We re‐evaluated this classic example alongside a second arboreal group of lizards that has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 155 publications
0
6
1
Order By: Relevance
“…A recent study of dewlap size allometry in Caribbean anoles reported surprising evidence for hypo -allometry, i.e. dewlap size was proportionately smaller with increasing body size [14]. This result was especially surprising as it was counter to all other studies (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…A recent study of dewlap size allometry in Caribbean anoles reported surprising evidence for hypo -allometry, i.e. dewlap size was proportionately smaller with increasing body size [14]. This result was especially surprising as it was counter to all other studies (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…[11][12][13]), including our results here. The paper introduced a new method based on measurements taken from videos of lizards displaying in nature [14]. Though an innovative and potentially important method, when we examined the underlying data associated with the paper, we found that the dewlap size measurements are vastly larger than our measurements of individuals of the same species (see electronic supplementary material).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations